Digital Marketing Tools in an Advertising Campaign in Foreign Markets - Rozhko Viktor I.; Shchelkova Anna V. (Problemi Ekonomiki)
This article reviews advertising tools and analyzes their importance. The advantages of advertising media have been researched and their characteristics have been provided. Attention is also paid to modern advertising campaign tools that companies use to promote their products and services in foreign markets. With an emphasis on the dynamics of globalization and digitalization, the latest trends and innovations in the field of marketing and advertising are analyzed, allowing to effectively reach target audiences in different parts of the world. Particular attention is paid to how companies adapt their advertising strategies to changing consumer requirements and preferences in international markets and, further, how technological innovations affect the choice of tools for advertising campaigns. Various tools are described, including digital media, social media networks, influencer marketing, contextual advertising, SEO optimization, and other digital channels that currently are at the forefront of advertising activity. There is a strong focus on the interactive and personalized aspects of digital marketing, which provide businesses with the opportunity to build deeper and more emotional connections with their customers. Previously unexplored parts of the general problem are highlighted, in particular, the difficulties of measuring the effectiveness of various advertising tools in international markets and the adaptation of marketing strategies to the cultural characteristics of different countries. The aim of the article is to determine the most efficient modern tools of the advertising campaign for the international market and to develop recommendations for companies seeking to expand their presence abroad; outlining the methodological and practical aspects of the process of managing marketing tools at enterprises. The efficiency of each tool was evaluated on the basis of information obtained from scientific sources, using observational and abstract methods, as well as comparative analysis. Different levels of strategies are considered, along with the main tools for each level. The major performance indicators of the marketing campaign are analyzed in order to determine further directions for improving the campaign. When implementing any marketing campaign in the digital space, digital tools create many opportunities and threats for companies that need to be considered in order to minimize possible setbacks at launch.